Secrets in banking practice - Uma, Idika Kalu (Abuja, Nigeria : A.B.C. Prints and Publishing, 2014)
The book throws up many secrets in banking practice and brings considerable awareness to both the bank customer and the banker of banking laws, rules, regulations, processes and procedures that constitute bankng practice.
oif 09/09/14, ijb 13/03/2019
Loans
Keywords: Banks and banking; Banking law; Banking practice